2023
DOI: 10.1007/s10654-023-00969-7
|View full text |Cite
|
Sign up to set email alerts
|

The carcinogenicity of opium consumption: a systematic review and meta-analysis

Abstract: The carcinogenicity of opium consumption was recently evaluated by a Working Group convened by the International Agency for Research on Cancer (IARC). We supplement the recent IARC evaluation by conducting an extended systematic review as well as a quantitative meta-analytic assessment of the role of opium consumption and risk for selected cancers, evaluating in detail various aspects of study quality on meta-analytic findings. We searched the published literature to identify all relevant studies on opium cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…A working group of the International Agency for Research on Cancer (IARC) evaluated the carcinogenicity of opium and found it to be carcinogenic to bladder cancer. This nding was similarly con rmed by an additional meta-analysis based on this work [53,54]. Our study also validated this nding based on a European population.…”
Section: Discussionsupporting
confidence: 88%
“…A working group of the International Agency for Research on Cancer (IARC) evaluated the carcinogenicity of opium and found it to be carcinogenic to bladder cancer. This nding was similarly con rmed by an additional meta-analysis based on this work [53,54]. Our study also validated this nding based on a European population.…”
Section: Discussionsupporting
confidence: 88%
“…Studies assessing the same risk factor often had a different study design, geographical location, exposure measurement, exposure assessment category, exposure intensity, and confounding factors adjusted for, and variability in sample size (most studies were small case–control studies), therefore caution is needed when interpreting the magnitude of the risk estimates. Similar limitations regarding differences in exposure assessment quality were reported in a recent systematic review on the carcinogenicity opium consumption [ 89 ] None of the studies directly measured carcinogen levels in tobacco, alcohol or indoor smoke. Acetaldehyde levels of alcohol may have differed, especially in home-brewed beer.…”
Section: Discussionmentioning
confidence: 79%
“…In 2019, over 100 million people smoked regularly, with nearly 80000 deaths due to smoking. Smoking is the main risk factor for male deaths and disability adjusted life years [33,34] . There are relatively few deaths among women due to the low smoking rate [35] .…”
Section: Discussionmentioning
confidence: 99%